Agricultural Transformation, Economic Growth, and Poverty in Indonesia - Askar, Media Wahyu (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2015)
This paper explores the link between agricultural transformation, economic growth and poverty in Indonesia. Based on descriptive analysis, it shows that the Indonesia’s economic growth and poverty reduction performance are more influenced by the service sector than the agriculture sector. The two major challenges to implement agricultural transformation in Indonesia are the limited availability of land and agricultural contract issue. To address these challenges, a gradual change is the best solution. The fixed rent scheme should be introduced properly to the society so as to increase the agricultural production, while support from the government is needed to help the smallholder’s farmers to avoid poverty